2015
DOI: 10.1371/journal.pone.0123445
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Mating System Are Regulated by Fecundity in Shorea curtisii (Dipterocarpaceae) as Revealed by Comparison under Different Pollen Limited Conditions

Abstract: The maintenance of mixed mating was studied in Shorea curtisii, a dominant and widely distributed dipterocarp species in Southeast Asia. Paternity and hierarchical Bayesian analyses were used to estimate the parameters of pollen dispersal kernel, male fecundity and self-pollen affinity. We hypothesized that partial self incompatibility and/or inbreeding depression reduce the number of selfed seeds if the mother trees receive sufficient pollen, whereas reproductive assurance increases the numbers of selfed seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 67 publications
0
8
0
1
Order By: Relevance
“…We found that lower initial height had a significantly negative effect on seedling survival, which may be because height is advantageous to competing for light on the forest floor (Takeuchi et al 2005). Fitness reduction of inbred individuals at early life stages was commonly found in previous studies of tropical tree species, such as a high abortion rate (Hufford and Hamrick 2003), seed maturation failure (Ghazoul et al 1998;Nagamitsu et al 2000;Tani et al 2015), smaller seed mass (Naito et al 2005), low germination rate (Naito et al 2005;Ismail et al 2014), and lower plant height (Rymer et al 2015).…”
Section: Inbreeding Depressionmentioning
confidence: 55%
“…We found that lower initial height had a significantly negative effect on seedling survival, which may be because height is advantageous to competing for light on the forest floor (Takeuchi et al 2005). Fitness reduction of inbred individuals at early life stages was commonly found in previous studies of tropical tree species, such as a high abortion rate (Hufford and Hamrick 2003), seed maturation failure (Ghazoul et al 1998;Nagamitsu et al 2000;Tani et al 2015), smaller seed mass (Naito et al 2005), low germination rate (Naito et al 2005;Ismail et al 2014), and lower plant height (Rymer et al 2015).…”
Section: Inbreeding Depressionmentioning
confidence: 55%
“…The classic neighborhood model assumes that s, m and c are the same for all sampled families. Here, as in earlier studies (Chybicki & Burczyk, 2013; Chybicki et al, 2019; Tani et al, 2015), we assumed that these probabilities might show inter‐family variation. To do so, a vector }{sj,mj,cj for the j‐th family was assumed to follow a Dirichlet distribution with three hyper‐parameters }{αs,αm,αc.…”
Section: Methodsmentioning
confidence: 91%
“…In addition, we cannot exclude potential effects of variation in null alleles across species, which could mask inbreeding effects. Other studies have proposed self‐fertilization and apomixis to be potentially important to dilute the effects of seedling predators (Ghazoul & Satake, ; Tani et al, ). It would be interesting to explore these different stages of reproduction in more detail in future studies.…”
Section: Discussionmentioning
confidence: 99%